1996
DOI: 10.1063/1.117727
|View full text |Cite
|
Sign up to set email alerts
|

Deep-level defects and n-type-carrier concentration in nitrogen implanted GaN

Abstract: We analyzed the intrinsic defects and the n-type-carrier concentration generated by nitrogen ion implantation in n-type GaN by deep-level-transient spectroscopy and by capacitance–voltage measurements, respectively. The samples were grown on sapphire by metalorganic vapor-phase epitaxy. Nitrogen implantation with different ion doses and postimplantation rapid-thermal annealing (RTA) were investigated. We observed a growing n-type-carrier concentration and increasing defect concentration with increasing nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
90
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 0 publications
14
90
1
Order By: Relevance
“…3, is close to E 3 ͑0.665 eV͒ 3 and D3 ͑0.67 eV͒. 4 Trap B, peaked at ϳ335 K with E T ϭ0.62 eV and T ϭ7.4 ϫ10 Ϫ15 cm 2 , which is close to E 2 ͑0.58 eV͒, D2 ͑0.60 eV͒, and DLN 3 ͑0.59 eV͒ reported by Hacke et al, 3 Haase et al, 4 and Götz et al, 5 respectively, was also found 7 to be a dominant trap in both MOCVD and HVPE GaN layers, with trap densities from 1 to 2ϫ10 14 cm Ϫ3 . Trap D, peaked at ϳ160 K with E T ϭ0.24 eV and T ϭ2.0ϫ10 Ϫ15 cm 2 , which is close to E 1 ͑0.264 eV͒ 3 and DLN 1 ͑0.25 eV͒, 5 was also found 7 in both MOCVD and HVPE GaN, but with trap densities in the low-10 14 cm Ϫ3 .…”
Section: T Mmentioning
confidence: 64%
See 3 more Smart Citations
“…3, is close to E 3 ͑0.665 eV͒ 3 and D3 ͑0.67 eV͒. 4 Trap B, peaked at ϳ335 K with E T ϭ0.62 eV and T ϭ7.4 ϫ10 Ϫ15 cm 2 , which is close to E 2 ͑0.58 eV͒, D2 ͑0.60 eV͒, and DLN 3 ͑0.59 eV͒ reported by Hacke et al, 3 Haase et al, 4 and Götz et al, 5 respectively, was also found 7 to be a dominant trap in both MOCVD and HVPE GaN layers, with trap densities from 1 to 2ϫ10 14 cm Ϫ3 . Trap D, peaked at ϳ160 K with E T ϭ0.24 eV and T ϭ2.0ϫ10 Ϫ15 cm 2 , which is close to E 1 ͑0.264 eV͒ 3 and DLN 1 ͑0.25 eV͒, 5 was also found 7 in both MOCVD and HVPE GaN, but with trap densities in the low-10 14 cm Ϫ3 .…”
Section: T Mmentioning
confidence: 64%
“…Based on the effects of 270-keV N 2ϩ implantation and annealing, Haase et al have suggested that two centers, D2 and D3, with activation energies of 0.60 and 0.67 eV, are the N antisite and N interstitial, respectively. 4 Recently, some of the present authors have reported an electron-irradiation-induced trap, located at E C -0.18 eV, in both MOCVD and HVPE GaN. This trap is most likely associated with the N vacancy.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…In a later study, Fang et al suggested the peak to be related to the divacancy V N -V Ga . 18 The trap D3 at $Ec-0.60 eV has been previously reported 10,11,16,19,20 and one of the suggested defect models is the N antisite (N Ga ). 19 However, later studies of electronirradiated HVPE-grown GaN 21 ruled out the model of a simple intrinsic defect since no change of the concentration was observed after irradiation.…”
mentioning
confidence: 86%